Common bottlenose dolphin (Tursiops truncatus) abundance and distribution patterns in St Andrew Bay, Florida, USA. Issue 3 (20th January 2019) - Balmer, Brian; Watwood, Stephanie; Quigley, Brian; Speakman, Todd; Barry, Kevin; Mullin, Keith; Rosel, Patricia; Sinclair, Carrie; Zolman, Eric; Schwacke, Lori
Abstract: Common bottlenose dolphins ( Tursiops truncatus ) are found in temperate and tropical waters of the world across a wide range of habitats. Along Florida's north‐western coast, this species resides in the bays, sounds, and estuaries (BSE) and coastal (CST) waters of the northern Gulf of Mexico. The National Marine Fisheries Service has identified one CST (Northern Coastal Stock) and seven adjacent BSE dolphin stocks, including the St Andrew Bay BSE Stock. Baseline data are critical to assess the impacts of ongoing and future anthropogenic stressors on these stocks. Currently, there is no comprehensive abundance estimate for the St Andrew Bay BSE Stock, and there are limited data on distribution patterns and site fidelity for this stock. In addition, little is known about the Northern Coastal Stock hypothesized to range from the Big Bend of Florida to the Mississippi River Delta, inclusive of the CST waters adjacent to St Andrew Bay. The goals of this study were to conduct photographic‐identification surveys during 2015 and 2016 to determine abundance, distribution, and site fidelity of common bottlenose dolphins in the St Andrew Bay BSE Stock over four primary periods (July and October 2015, and April and October 2016). St Andrew Bay BSE dolphin abundance was lowest in April 2016 (199, 95% confidence interval [CI] 173–246), followed by July 2015 (249, 95% CI 199–338), and highest in October 2015 (299, 95% CI 259–361) and October 2016 (315, 95% CI 274–378). Few individuals were sighted in both BSE and CST waters ( N  = 25/353; 7%), and this fact, taken in tandem with limited connections between the BSE and CST environments, suggests that there may be minimal overlap between the St Andrew Bay BSE and Northern Coastal Stocks.